Pupillometric findings in ATTRv patients and carriers: results from a single-centre experience. (2nd October 2022) - Romano, Angela; Guglielmino, Valeria; Di Paolantonio, Andrea; Bisogni, Giulia; Sabatelli, Mario; Della Marca, Giacomo; Minnella, Angelo Maria; Maceroni, Martina; Bellavia, Simone; Scala, Irene; Sabatelli, Eleonora; Rollo, Eleonora; et al.
Abstract: Introduction: Hereditary transthyretin amyloidosis (ATTRv) is a treatable multisystemic disease with great phenotypic heterogeneity. Among extra-neurological features, pupillary abnormalities have been reported, either related to amyloid deposition in the eye or to a progressive autonomic neuropathy. Objective: To evaluate the role of automated pupillometry, a non-invasive and rapid test able to provide objective and reproducible data on pupil size and reactivity, as a marker of disease severity in late-onset ATTRv patients. Patients and methods: We performed automated pupillometry on a cohort of ATTRv patients and pre-symptomatic TTR mutation carriers and compared results to healthy controls. An exhaustive clinical and instrumental evaluation was performed on all enrolled subjects. Results: A statistically significant difference in most pupillometry parameters was found in ATTRv patients as compared to both carriers and healthy controls. Moreover, in ATTRv patients, we found a significant correlation between many pupillometry findings and disease duration, as well as widely accepted clinical scales and investigations (NIS, Sudoscan from feet, and Norfolk QoL-DN questionnaire). Conclusions: We suggest pupillometry may play a role as a reliable and non-invasive biomarker to evaluate ATTRv disease severity and monitor its progression.